Integrated Metabolomics and Network Pharmacology Analysis Immunomodulatory Mechanisms of Qifenggubiao Granules - Guo, Bindan; Dong, Wenting; Huo, Jinhai; Sun, Guodong; Qin, Zhiwei; Liu, Xiaodong; Zhang, Bihai; Wang, Weiming (Frontiers in Pharmacology, 2022)
Qifenggubiao granules (invention patent number: CN1325098C, approval number: Sinopharm Zhunzi B20020410) is a new Chinese medicine independently developed by Heilongjiang Academy of Traditional Chinese Medicine, which combines the essence of Yupingfeng powder and Shengmaiyin , and has been included in the 2020 edition of Chinese Pharmacopoeia. It has remarkable pharmacodynamic results and conclusive clinical effects in the treatment of respiratory diseases such as allergic rhinitis and chronic cough. Previous pharmacological studies have shown that it has immunomodulatory effect, but its immunomodulatory mechanism is still unclear.